Sound Correspondences of Modern Standard Arabic Moroccan Arabic and Najdi Arabic - Darsita Suparno; Ulil Abshar; M. Wildan; Tri Pujiati (Sunan Kalijaga: International Journal of Islamic Civilization, 2020)
This paper studies the process of sound correspondences that occur in Modern Standard Arabic (MSA), Moroccan Arabic (MAR), and Najdi Arabic (NAR). It attempts to find answers for the following questions: a) What are the identical word pairs, words couples that have a phonemic correspondence, a phonetic similarity, and a pair of words that contains difference of one phoneme, b) What are the process of morphophonemic in the form of assimilation, metathesis, and epenthesis. It is addressed to portray the process of morphophonemic assimilation, metathesis and epenthesis in three Arabic languages using Crowley’s theory. This study used 207 of Morris Swadesh's basic vocabulary as the key standard procedure for collecting data. The criteria adopted to analyze the data were orthographic, sound-change, phonological, and morpheme contrast. This research used descriptive qualitative method. The source of the data was basic-word vocabulary. The data were gathered from three dictionaries as sources to get information. The data were analyzed by using structural linguistics, especially phonology, morphology, and semantics. This investigation informed several aspects of findings such as identifying prefixes, suffixes, assimilation, metathesis, and epenthesis. Using the Swadesh vocabulary list, the results of this study found 207 vocabularies for each language. By analyzing parts of speech, it was found that these vocabularies can be classified into five-word classes, namely, nouns, pronouns, verb, adjectives, adverbs, and determiners.